Традиционное еврейское образование в Литве - Лемпертене, Лариса (Slavistica Vilnensis, 2000)
The article gives a description of the traditional system of Jewish religious education in Lithuania. This system is a continuation and further development of the system which was created and shaped in Ashkenaz (the Hebrew name for West, Central and East Europe) from the Middle Ages onward. Lithuania was renowned for its Jewish scholars and educational institutions. The article contains a survey of traditional forms of Jewish education for young children, teenagers and adults, as well as of the opportunities for individuals to enrich and improve their knowledge without attending any specific academic/religious institution. The main feature of traditional Jewish life in Lithuania was that most males were not only literate, but also very well acquainted with Jewish classical texts, because knowledge conferred far more prestige than a high material standard of living. Even women were usually educated, although not to the extent that was usual for men. The article deals specifically with the most renowned form of Jewish education in Lithuania, the yeshiva (religious academy). A number of Lithuanian yeshivas were famous all over the world, especially in the 19th and early 20th centuries. Foremost among these was the famous Volozhin Yeshiva ‘Etz hayim’, founded in 1802 by Rabbi Hayim from Volozhin, a disciple of the Vilna Gaon. This and other Lithuanian yeshivas became a symbol of Lithuanian Jewish scholarship because of their high academic reputation and the authority of their founders and staff; they attracted students not only from Lithuania itself, but also from other countries.